Professing to learn : creating tenured lives and careers in the American research university - Neumann, Anna (Johns Hopkins University Press, 2009)
Research, teaching, service, and public outreach—all are aspects of being a tenured professor. But this list of responsibilities is missing a central component: actual scholarly learning—disciplinary knowledge that faculty teach, explore in research, and share with the academic community. How do professors pursue such learning when they must give their attention as well to administrative and other obligations? Professing to Learn explores university professors' scholarly growth and learning in the years immediately following the award of tenure, a crucial period that has a lasting impact on the academic career. Some launch from this point to multiple accomplishments and accolades, while others falter, their academic pursuits stalled. What contributes to these different outcomes? Drawing on interviews with seventy-eight professors in diverse disciplines and fields at five major American research universities, Anna Neumann describes how tenured faculty shape and disseminate their own disciplinary knowledge while attending committee meetings, grading exams, holding office hours, administering programs and departments, and negotiating with colleagues. By exploring the intellectual activities pursued by these faculty and their ongoing efforts to develop and define their academic interests, Professing to Learn directs the attention of higher education professionals and policy makers to the core aim of higher education: the creation of academic knowledge through research, teaching, and service.